Hyperphosphorylation by Cyclin B/CDK1 in Mitosis Resets CUX1 DNA Binding Clock at Each Cell Cycle - Sansregret, Laurent (American Society for Biochemistry and Molecular Biology, 2010)
The p110 CUX1 homeodomain protein participates in the activation of DNA replication genes in part by increasing the affinity of E2F factors for the promoters of these genes. CUX1 expression is very weak in quiescent cells and increases during G(1). Biochemical activities associated with transcriptional activation by CUX1 are potentiated by post-translational modifications in late G(1), notably a proteolytic processing event that generates p110 CUX1. Constitutive expression of p110 CUX1, as observed in some transformed cells, leads to accelerated entry into the S phase. In this study, we investigated the post-translation regulation of CUX1 during mitosis and the early G(1) phases of proliferating cells. We observed a major electrophoretic mobility shift and a complete inhibition of DNA binding during mitosis. We show that cyclin B/CDK1 interacts with CUX1 and phosphorylates it at multiple sites. Serine to alanine replacement mutations at 10 SP dipeptide sites were required to restore DNA binding in mitosis. Passage into G(1) was associated with the degradation of some p110 CUX1 proteins, and the remaining proteins were gradually dephosphorylated. Indirect immunofluorescence and subfractionation assays using a phospho-specific antibody showed that most of the phosphorylated protein remained in the cytoplasm, whereas the dephosphorylated protein was preferentially located in the nucleus. Globally, our results indicate that the hyperphosphorylation of CUX1 by cyclin B/CDK1 inhibits its DNA binding activity in mitosis and interferes with its nuclear localization following cell division and formation of the nuclear membrane, whereas dephosphorylation and de novo synthesis contribute to gradually restore CUX1 expression and activity in G(1).